(untitled) (Texas Journal of Medical Science, 2024)
The article presents a scientific review of the interrelation between gastrointestinal tract (GIT) pathologies and the development of inflammatory diseases of periodontal tissues. It examines how changes in the GIT, including dysfunctions of the immune and endocrine systems, affect the state of the periodontium, enhancing the development of diseases such as gingivitis and periodontitis. Special attention is given to gastroduodenal diseases, their prevalence, and their impact on the periodontium. The significance of a comprehensive approach in the diagnosis and treatment of patients with periodontal diseases and GIT disorders is emphasized. The mechanisms of interaction between these systems are analyzed, including changes in microcirculation, endotoxicosis, and the role of neurohumoral regulation and psychosomatic factors. Data on the increased frequency of periodontitis in patients with GIT disorders are discussed, including disorders related to endocrine system functions, as in the case of type II diabetes. The influence of Helicobacter pylori infection on periodontal diseases is discussed, highlighting the need for an integrated medical approach in treatment. Clinical signs and problems associated with gastroesophageal reflux disease (GERD) and their impact on periodontal health are also presented. The article underscores the importance of considering these interrelations in medical practice for effective diagnosis and treatment